Universal Time variations in the magnetosphere - Lockwood, Mike; Milan, Stephen E. (Frontiers in Astronomy and Space Sciences, 2023)
We study the dependencies of Earth’s magnetosphere on Universal Time, UT. These are introduced because Earth’s magnetic axis is not aligned with the rotational axis and complicated because it is eccentric, which makes the offset of the magnetic and rotation poles considerably greater in the Southern hemisphere and the longitudinal separation of the magnetic poles less than 180°: hence consequent UT variations in the two hemispheres are not in equal in amplitude nor in exact antiphase and do not cancel, as they would for a geocentric dipole. We use long series of a variety of geomagnetic data to demonstrate the inductive effect of motions of the polar caps in a “geocentric-solar” frame, which is phase-locked to the Russell-McPherron (R-M) effect on solar-wind magnetosphere coupling. This makes the response of the magnetosphere-ionosphere system different for the two polarities of the Y-component of the Interplanetary Magnetic Field in the GSEQ reference frame, explaining the difference in response to the March and September equinox peaks in solar wind forcing. The sunward/antisunward pole-motion effect is detected directly in satellite transpolar voltage data and is shown to have a greater effect on the geomagnetic data than the full dipole tilt effect which generates the equinoctial pattern, the potential origins of which are discussed in terms of the dipole tilt effect on ionospheric conductivities and the stability of the near-Earth tail. Persistent UT variations in Region-1 and Region-2 field-aligned currents and in partial ring current indices are presented: their explanation is an important challenge for numerical modelling of the magnetosphere-ionosphere-thermosphere system which we need to quantify the relative contributions of the various mechanisms and to give understanding of the effect of arrival time on the response of the system to large, geoeffective disturbances in interplanetary space. Plain language summary: The effect on terrestrial space weather of Earth’s magnetic axis not being aligned with the rotational axis is investigated. It is complex because not only do these two axes not align in direction (the “dipole tilt”), the magnetic axis does not pass through the centre of the Earth, which sets a requirement for an “eccentric” model of the field and not the commonly-used “geocentric” one. For many years, it has been known that the dipole tilt gives a peak in geomagnetic activity at the equinoxes (the semi-annual variation) through the “Russell-McPherron” (R-M) effect. However, although the variation with Universal Time is consistent with the R-M effect for the September equinox, it is not for the March equinox. We here solve this long-standing puzzle by investigating the effects of the motions of the two poles in a frame fixed with respect to both the Earth and the Sun for an eccentric dipole model. But solving one puzzle generates many others. We present observations of the Universal Time variations that these mechanisms combine to generate, which set an important challenge to the numerical modelling of the near-Earth space environment.